(3aJM GdJMaI hEVGAI GdTQaIs - (3eMeO Hf EHQGgje Hf YHGOs
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi Gddg YR hLd eMeO Hf EHQGgje Hf YHGO hHYO aEfi deG QCjJ GdeLehY GdeSei HJMaI Gdehabjf GdeMHjf dSfI SjO GdeQSdjf s
(3BNQgG (B:s
(3aEf GdYde GdeMbb CfG HeYRd Yfg hGdLgd Ted gPG GdhLhO GfJgi s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs